-6a+4(7+3a)=2(1+4a)

Simple and best practice solution for -6a+4(7+3a)=2(1+4a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a+4(7+3a)=2(1+4a) equation:



-6a+4(7+3a)=2(1+4a)
We move all terms to the left:
-6a+4(7+3a)-(2(1+4a))=0
We add all the numbers together, and all the variables
-6a+4(3a+7)-(2(4a+1))=0
We multiply parentheses
-6a+12a-(2(4a+1))+28=0
We calculate terms in parentheses: -(2(4a+1)), so:
2(4a+1)
We multiply parentheses
8a+2
Back to the equation:
-(8a+2)
We add all the numbers together, and all the variables
6a-(8a+2)+28=0
We get rid of parentheses
6a-8a-2+28=0
We add all the numbers together, and all the variables
-2a+26=0
We move all terms containing a to the left, all other terms to the right
-2a=-26
a=-26/-2
a=+13

See similar equations:

| 4(4x+4)=64 | | 5/4y=5/6 | | 2(x=7)=28 | | |4x-10|=22 | | 1/300+1/200=1/x | | x^2+11=144 | | 28=t-50 | | -20=z-9 | | 7^x-1^2=100 | | 2bb=6 | | 6(x+8)=37 | | 6x+15+4x+35=180 | | |4x-8|=-28 | | 2y^2=6y-95 | | 6(x+8)=34 | | s+23=19 | | -17=4s-1 | | 4x-9=3x-23 | | v^2=12+v | | -18-6y=7(4y+3) | | 10x-9=6x+2 | | 5x+4+8x-11=180 | | p-28=-13 | | 3/4x-5=1/2x+2 | | 10=1/2t+18 | | -3(k-6)+k=-4(1+k) | | 35x3=x | | 3g+15=60 | | 8=g2 | | 23x-27=6x-13 | | 91=g44 | | (18/54)=(10/x) |

Equations solver categories